Podnikatelský záměr – vybudování areálu Freedomků - Uherková, Veronika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Předmětem této bakalářské práce je vytvoření podnikatelského záměru na vybudování areálu Freedomků v oblasti Pasohlávek. Jedná se o areál se sedmi stylovými domky, které budou sloužit k pronájmu ubytování pro širokou veřejnost. V první části vychází podnikatelský plán ze zpracovaných teoretických poznatků, ve druhé části poté z vypracovaných analýz a průzkumů vnitřního a vnějšího prostředí. Cílem práce je zjistit a posoudit, zda je podnikatelský záměr správně zpracovaný a v samotném závěru také reálný.

The theme of this bachelor’s thesis is to create a business plan for opening the compound of Freedomky houses in Pasohlávky area. It is the campus with four small houses, which will be designated for renting of accommodation to general public. In the introductory part the business plan is based on complied theoretical knowledge, in the second part it is based on analysis and research of external and internal environment of company. The aim of the thesis is to identify and assess the preparation and practicability of the business plan and in the end the fact if the business plan will be also actually real.
Business Plan – The Construction of the Freedomky Houses Campus
Keywords: Freedomky; podnikání; podnikatelský plán; finanční plán; SWOT analýza; Freedomky houses; business; business plan; financial plan; SWOT analysis